Et3N/DMSO-supported one-pot synthesis of highly fluorescent β-carboline-linked benzothiophenones via sulfur insertion and estimation of the photophysical properties - Singh, Dharmender; Kumar, Vipin; Singh, Virender (Beilstein Journal of Organic Chemistry, 2020)
A robust transition-metal-free strategy is presented to access novel β-carboline-tethered benzothiophenone derivatives from 1(3)-formyl-β-carbolines using elemental sulfur activated by Et3N/DMSO. This expeditious catalyst-free reaction proceeds through the formation of β-carboline-based 2-nitrochalcones followed by an incorporation of sulfur to generate multifunctional β-carboline-linked benzothiophenones in good to excellent yields. The synthetic strategy could also be extended towards the synthesis of β-carboline-linked benzothiophenes. Moreover, the afforded products emerged as promising fluorophores and displayed excellent light-emitting properties with quantum yields (ΦF) up to 47%.
Keywords: benzothiophene; β-carboline; metal-free; photophysical properties; sulfur insertion